Faktor-faktor yang Mempengaruhi Penggunaan Rokok Elektrik di Kalangan Komunitas Vape Muda - Agus Sri Banowo; Nazhifa Fauziyah; Boby Febri Krisdianto (Universitas Pahlawan Tuanku Tambusai, 2025)
The increase in e-cigarette users in society continues to grow, which can endanger bodily health. This study aims to determine the factors associated with e-cigarette users in the